Study of Silver Ions Diffusion into TiO2NT Using Finite Elements Method - Pilonetto, Luis Felipe; Sikora, Mariana de Souza (Orbital: The Electronic Journal of Chemistry, 2019)
The purpose of this paper is to study the diffusion of silver ions, Ag+, into TiO2 nanotubes, using Fick’s second law. The mathematical simulations were carried out using the finite element method to solve this partial differential equation. A single nanotube, immersed in an aqueous solution containing Ag+ ions, composes the physical two-dimensional model. The most relevant results show that the system final concentration can be calculated in the function of solution initial concentration, of solution volume and nanotube volume. The equation obtained can be generalized to the study of diffusion for other ions in aqueous solution through nanotubular structured materials, because the equation does not take into account the diffusion coefficient of the ions. The height of nanotube is exponentially proportional to the equilibrium time, proving the relation of height with the diffusion course. On the other hand, the diameter of nanotube does not have a significant relationship with the equilibrium time. These results indicate that for ions incorporation into materials, with nanotubular structure, it should prioritize experimental conditions that favor the vertical growth of the nanotubes.DOI: http://dx.doi.org/10.17807/orbital.v11i6.1241